Quantitative evaluation and correlation of serum glycoconjugates: Protein bound hexoses, sialic acid and fucose in leukoplakia, oral sub mucous fibrosis and oral cancer - Bose, K. Subhash Chandra (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Cancer is one of the most common causes of mortality and morbidity today, with more than 10 million new cases and more than 6 million deaths each year worldwide. Globally Oral Cancer is the sixth most common cause of cancer related death. India accounts for 86% of the world's oral cancer cases. Often it proceeds by pre cancerous conditions and lesions. In search for biological markers with diagnostic value, we investigated serum glycoconjugates like protein bound hexoses, fucose and sialic acid in these diseases. MATERIALS AND METHODS: For this Study 27 newly diagnosed Oral leukoplakia, 27 OSMF and 26 Oral Cancer patients, 40 healthy controls who are non tobacco users and 40 healthy controls who are tobacco users were selected. In all these groups we estimated serum glycoconjugates. RESULTS: We observed no difference in serum glycoconjugates levels between tobacco and non tobacco controls (P > 0.05), but very high levels in oral cancer, Leukoplakia and oral sub mucous fibrosis (OSMF) patients (P < 0.001) when compared to control groups. Fucose levels were significant (P < 0.05) of all the glycoconjugates between OSMF and Leukoplakia. CONCLUSION: The serum glycoconjugates whose levels were very high in OSMF, Leukoplakia and Oral Cancer, do have a significant diagnostic and prognostic value in these diseases.